Ketorolac Administration After Colorectal Surgery Increases Anastomotic Leak Rate: A Meta-Analysis and Systematic Review - Chen, Wen; Liu, Jing; Yang, Yongqiang; Ai, Yanhong; Yang, Yueting (Frontiers in Surgery, 2022)
Objective: The purpose of the meta-analysis was to evaluate the relationship between ketorolac and anastomotic leak rate after colorectal surgery. Methods: Studies were comprehensively identified by searching Web of Science, Embase, and PubMed databases up to May 31th, 2020. The meta-analysis was carried out to compare the anastomotic leak rate between ketorolac use group and controls groups. The Newcastle-Ottawa Scale was applied to assess methodological quality. Chi-squared Q test and I2 statistics were applied to evaluate statistical heterogeneity. Subgroup analyses were conducted and publication bias was assessed by Egger's test. Results: Seven studies were finally entered in the meta-analysis. The use of ketorolac after surgery increases the risk of anastomotic leakage [OR=1.41 (0.81–2.49), Z=1.21, P=0.23]. Statistically significant heterogeneity was observed across these studies (I2 = 0%, P =0.51). The results of subgroup analysis showed that the risk of anastomotic leak was significantly increased in use of ketorolac, not in use of ketorolac plus morphine, in case-control and retrospective cohort studies, and also in Canada and USA patients with ketorolac (all P<0.05). There was no significant publication bias (P=0.126). Besides, The analysis of risk factors related to anastomotic leakage rate indicated that the total use of ketorolac was not associated with an increased risk of anastomotic leak (P>0.05). Conclusion: The meta-analysis might indicate that ketorolac exposure was associated with the risk of anastomotic leak.